(untitled) (ALMUSTOFA: Journal of Islamic Studies and Research, 2025)
Academic supervision serves as a strategic instrument for enhancing the quality of higher education, providing a mechanism to control, oversee, and continuously develop the planning, implementation, and evaluation of educational programs. This study aims to analyze effective academic supervision models that support the oversight and evaluation of educational programs, focusing on their implementation, supporting and inhibiting factors, and their contribution to academic quality and institutional accountability. Utilizing a qualitative approach through literature review and content analysis of various documentary sources, the findings indicate that collaborative and digital technology-based academic supervision models are highly effective in improving the quality of educational programs; supervision functions not only as a control mechanism but also as a medium for professional faculty development, instructional quality improvement, and the attainment of sustainable quality standards. Consequently, there is a need to strengthen data-driven and digital-based academic supervision models to ensure that evaluation transcends administrative formality and actively fosters pedagogical innovation and academic competitiveness. This research contributes by specifically identifying collaborative and digital models as the most effective, providing a practical framework for higher education leaders to redesign their oversight systems by shifting from an administrative focus toward data-driven professional development, which directly supports instructional innovation and institutional accountability to ensure sustainable academic quality.